Bomb radiocarbon model and stable isotopes from A radiocarbon bomb pulse model for estimating the age of North Atlantic cetaceans - Eva Garde; Susanne Ditlevsen; Jesper Olsen; Mads Peter Heide-Joergensen (2024)
Final_2Supplementary material_Oct4docx.docx